Investigação da contaminação bacteriana em concentrados plaquetários e avaliação de técnicas convencionais - Martini, Rosiéli (2012)
Blood transfusions have always been great support for monitoring the treatment of cancer, especially patients in the sectors of hematology-oncology, but still stand out as a major source of transmission of infectious diseases, today the bacteria. Platelet concentrates (PCs) are the blood components with higher frequency of bacterial contamination and are responsible for the vast majority of septic transfusion reactions. Bacterial infection is a major cause of morbidity and mortality due to platelet transfusions. Gram-positive bacteria, particularly Staphylococcus epidermidis, are mainly responsible for the contamination of PCs. Therefore, this study aimed to determine the prevalence of bacterial contamination in PCs, the isolation and identification of microorganisms found. In addition, we sought to identify septic transfusion reactions and to evaluate conventional techniques for bacterial detection. A total of 691 samples of PCs (665 whole blood-derivaded platelets and 26 apheresis platelets) was analyzed. These samples were from the Blood Center of the State of Rio Grande do Sul (HEMORGS), located in Santa Maria, Rio Grande do Sul. Were employed culture techniques qualitative, quantitative, daily growth and also metabolic markers for the detection of bacteria. Tests for identification of microorganisms were made by conventional techniques and the phenotypic and genotypic screening of septic reactions was performed by passive haemovigilance. The prevalence of bacterial contamination found in this study was 1.47% and S. epidermidis bacteria was responsible for all contamination. This prevalence is considered high when compared to recent studies conducted in other countries, in Brazil we have very few studies in this area. All samples were contaminated platelet random. The test metabolic markers were nonspecific for the detection of bacteria. There was a great difficulty in performing the daily growth of the technical methodology make it impossible to be proposed to HEMORGS. Through haemovigilance passive transfusion reactions were characterized and it was possible to confirm the occurrence of a septic transfusion reaction. Therefore, we suggest the combination of methodologies for the detection of bacterial contamination screening of PCs, since it is a health problem. The combination of culture systems can reduce the risks of transfusions contaminated CPs. We believe that the septic transfusion reactions can be minimized with early recognition by the clinical team.